Losartan: il valore clinico ed economico - Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2004)
Losartan is an angiotensin II receptor antagonist (ARB) that has been proven effective and well tolerated in the treatment of hypertension and in the reduction of global cardiovascular risk, but is more expensive than many alternatives. The present paper resumes its main pharmacological and clinical features, as a basis for analyzing its economical value. Despite the universally accepted relevance of good blood pressure control, hypertension is still undertreated and poorly controlled. Among the main reasons for this, poor adherence to therapeutic regimens plays a relevant role. Losartan and ARBs have been shown to be associated with compliance rates superior to those observed with any other antihypertensive drug class, due to an adverse events incidence similar to placebo and scarcity of relevant pharmacological interactions, and can therefor improve the cost-effectiveness of hypertension treatment. Several trials have indicated that losartan determines clinical benefits that go beyond its haemodynamic effect, such as renal protection, reduced incidence of stroke and cognitive improvement. The addition of losartan to conventional hypertensive therapy in diabetic patients with nephropathy has been estimated to induce net health cost savings in different settings, a relevant result, as very few medical interventions have demonstrated such a potential. To understand the real economical value of losartan, its drug acquisition costs have to be balanced against the benefits deriving from antihypertensive effectiveness, high compliance and non-haemodynamic target organ protection.